ChemInform Abstract: Chemical Expansion: Implications for Electrochemical Energy Storage and Conversion Devices. Issue 29 (July 2015) - Bishop, S. R.; Marrocchelli, D.; Chatzichristodoulou, C.; Perry, N. H.; Mogensen, M. B.; Tuller, H. L.; Wachsman, E. D.
Abstract Review: 196 refs.